Development of Web-Based Architectural Design - Aulia, Mohamad Donie; Aditia, R; Sir, B S; Albar, Chepi Nur; Dewi, Natasha Puspa; Mega, Raiswati Untsa; Ramazhany, Kinanti F (International Journal of Research and Applied Technology (INJURATECH), 2023)
This research examines digital marketing's influence in increasing sales and profit in the architectural design business. Information technology is developing rapidly nowadays. Its impact makes it easier for all community activities. The method in this research was qualitative. The study results show that the ARSITAG website is a good place for marketing architectural design products, and it concludes that digital marketing makes the architectural design marketing process easier and more efficient. It is because the conversion rate of architectural design projects through print and online media has increased rapidly. The ARSITAG website is a marketing strategy in design and development by making it easier for potential buyers to determine building designs